Chemistry teachers’ self-efficacy scale for differentiated instruction: Development and validation - Rais Assad Faiz; Hari Sutrisno (Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
This research aims to develop and validate a new instrument for measuring chemistry teacher’s self-efficacy for differentiated instruction. Data was collected using developed questions based on a literature study. The data were analyzed using exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and correlational techniques based on responses from 156 chemistry teachers in Yogyakarta who participated in an offline and online survey. The findings from EFA, CFA, and correlation analysis provide sufficient empirical evidence to support the convergent and discriminant validity of the instrument. The high Cronbach’s coefficient alpha values show the instrument’s good internal consistency and reliability. We documented a valid and reliable chemistry teachers’ self-efficacy for differentiated instruction with six constructs consisting of 22 items by integrating the evidence from theory and data. The six-factor scale is named "efficacy in differentiating the learning process, efficacy in differentiating learning content, efficacy in differentiating learning products, efficacy in identifying student differences, efficacy in assessment, and efficacy in differentiating the learning environment". This instrument enriches the theoretical understanding of teacher self-efficacy in differentiated instruction by providing a domain-specific measurement model tailored for chemistry education. Practically, the scale offers teacher educators, policymakers, and professional development programs a diagnostic tool to identify teachers’ strengths and areas needing support, enabling more targeted training interventions to enhance differentiated instruction in classroom practice.